In Vivo Assessment of Absorbable Knotless Barbed Suture for Single Layer Gastrotomy and Enterotomy Closure1. Issue 2 (1st February 2013) - Ehrhart, Nicole P.; Kaminskaya, Kristina; Miller, Jeffrey A.; Zaruby, Jeff F.
Abstract Objective To compare the performance of an absorbable barbed suture device to absorbable monofilament suture after single layer, appositional gastrotomy and enterotomy closure. Study Design Experimental comparative study. Animals Purpose‐bred adult mongrel hounds (n = 14). Methods Bursting strengths up to 250 mmHg of incisional closure with either monofilament or barbed suture in a simple continuous, appositional pattern at sites in the stomach (2), jejunum (4), and colon (4) were compared at postoperative Days 3, 7, and 14. Time for incisional closure was compared between materials. Results Bursting strength was not significantly different between gastrotomies/enterotomies closed with the monofilament suture or the barbed device. Closure time was significantly reduced with the barbed device in jejunal enterotomy closure. Conclusion The barbed device compared favorably with monofilament suture for gastrotomy and enterotomy (small intestine, colon) closure. Results demonstrate comparable burst strengths between monofilament suture and the barbed device. Closure time was significantly reduced in jejunum closure using the barbed device.